Patient Satisfaction with HIV/AIDS Services in Health Centers of East Shoa Zone, Oromia, Ethiopia: A Cross-Sectional Study - Temesgen Aferu Yilma; Gebremedhin Beedemariam Gebretekle; Teferi Gedif Fenta (SAGE Publishing, 2021)
Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) is a major public health, social, and economic problem in Ethiopia. Even though the government is working to scale up Anti-Retroviral Therapy (ART) services, patient loss to follow-up and ensuring adherence to ART regimens remain major challenges of the ART program in the country; little has also been done on the assessment of patient satisfaction on different HIV/AIDS service dimensions. This study aimed at assessing patient satisfaction with HIV/AIDS services in health centers of East Shoa Zone, Oromia region, Ethiopia. The study employed a cross-sectional survey between February and May 2017. Data was collected through exit interviews using five-point Likert scale-based questions and analyzed using Statistical Package for Social Sciences (SPSS) version 20. The overall mean patient satisfaction score was 3.16 (SD = 0.87) on a 1 to 5 scale. Availability of anti-Tuberculosis (anti TB) drugs in pharmacy was an item with the highest mean satisfaction score (4.18 ± 0.61) while waiting time to get pharmacy service was ranked least by the patients (mean score of 1.92, SD = 0.81). Merchants and students were more likely to be satisfied compared to other occupational groups. Overall, there was a wider gap in the study facilities concerning patient satisfaction and, therefore, health facility managers, Zonal and Woreda health offices, and Oromia Region Health Bureau should work in collaboration with other stakeholders to improve patient satisfaction with items for which the satisfaction score was low.